PENGARUH METODE EKSTRAKSI MINYAK PUPA ULAT JERMAN TERHADAP KOMPOSISI KIMIA - Erik Priyo Santoso; Farida Kusuma Astuti (BUANA SAINS, 2018)
The aim of this research is to know the extraction method of caterpillar pupa without detrimental to chemical composition to know the amount of pupa production of German caterpillar with two extraction methods per 100 grams of pupa To know the content of dry matter, organic matter, crude protein, crude fat, crude fiber and amino acid lysin, methionine, and vitamin E pupa oil of German caterpillar. The study was conducted from February to April 2017, at the Lab. Central University Tribhuwana Tunggadewi. Oil extraction analysis was conducted in the chemistry laboratory of Tribhuwana Tunggadewi University and chemistry laboratory of Poltek Malang. German caterpillar research material, German caterpillar pupa, pupa caterpillar germany extracted by maceration and sokletasi. German caterpillar pupa is obtained from German caterpillar breeders in Amadanom, Dampit, Malang Regency. This research uses two different extraction methods, namely cold extraction method (maseration method) and using heat method (soxhlet method). The conclusions of both research methods are known that the quantity of German caterpillar yield using soxhlet extraction method is more than the maceration extraction method. However, for the quality of the two methods it is still necessary to do further analysis to know the exact comparison of the two methods.